Sistem Pembelajaran di Pesantren Kebon Jambu al-Islami Babakan Ciwaringin Cirebon - Ratu Suntiah; H Maslani (UIN Sunan Gunung Djati Bandung, 2019)
This research departs from the view that education is an effort to preserve, transfer and transform values in all its aspects. In the context of improving education in pesantren institutions there needs to be developed. This study applies qualitative research methods. Therefore, the source of the data and the type of data determined by the researcher himself as the center of information and are purposive as long as they are considered representative. The researcher participated with the teachers and students in the implementation of educational learning at the Kebon Jambu al-Islami Islamic Boarding School in Ciwaringin Cirebon. The results showed that the background of the establishment of the Kebon Jambu al-Islami Islamic Boarding School in Ciwaringin Cirebon was due to the demands of the people who needed guidance to understand and practice Islamic teachings. The purpose of education is to form an intellectual cadre of ulama and asatidz. The subject matter taught is in the form of salaf and Khalaf books. The learning process consists of scheduled teaching and religious activities. Supporting factors for the implementation of activities are wise and sincere Kiai, many asatidz levels of education that have scholars, strategic geographical location, support of alumni.